Pseudo-random number generator RC4 period improvement - Chefranov, A. G.; Mazurova, T. A. (IEEE, 2006)
A new pseudo-random number generator algorithm RC4E, having: period significantly greater than RC4 has, is proposed. It is an extension of RC4. It uses RC4 as a main engine and Heap's algorithm as a second engine, providing enumeration of all possible permutations. Second engine is invoked periodically and it resets the current state of the main engine. Experiments, conducted on the both algorithms, showed their good statistical properties and practically same performance.
IEEE-TTTC International Conference on Automation, Quality and Testing, Robotics -- MAY 25-28, 2006 -- Cluj Napoca, ROMANIA
Keywords: Permutations